2020
DOI: 10.1111/1440-1681.13237
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial microvascular blood flow in skeletal muscle: Similarities and disparities to the hyperinsulinaemic‐euglycaemic clamp

Abstract: Skeletal muscle contributes to ~40% of total body mass and has numerous important mechanical and metabolic roles in the body. Skeletal muscle is a major site for glucose disposal following a meal. Consequently, skeletal muscle plays an important role in postprandial blood glucose homeostasis. Over the past number of decades, research has demonstrated that insulin has an important role in vasodilating the vasculature in skeletal muscle in response to an insulin infusion (hyperinsulinaemic‐euglycaemic clamp) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 116 publications
(313 reference statements)
1
9
0
Order By: Relevance
“…Lambadiari et al demonstrated that the macrovascular impairment influenced postprandial glucose disposal (with forearm muscle blood flow positively correlating with muscle glucose disposal) [24]. However, that study did not assess skeletal muscle specific MBF which is important because it is the microvasculature that controls glucose and insulin delivery to the myocyte [20,25,33,34] because not all vasodilators that augment large artery blood flow concomitantly increase glucose disposal to muscle. Methacholine and sodium nitroprusside can each increase large artery blood flow but can have opposing effects on muscle insulin-mediated glucose disposal [35,36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lambadiari et al demonstrated that the macrovascular impairment influenced postprandial glucose disposal (with forearm muscle blood flow positively correlating with muscle glucose disposal) [24]. However, that study did not assess skeletal muscle specific MBF which is important because it is the microvasculature that controls glucose and insulin delivery to the myocyte [20,25,33,34] because not all vasodilators that augment large artery blood flow concomitantly increase glucose disposal to muscle. Methacholine and sodium nitroprusside can each increase large artery blood flow but can have opposing effects on muscle insulin-mediated glucose disposal [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Skeletal muscle glucose uptake and utilisation occur via a combination of an increase in blood glucose concentration (mass action effect), and a rise in endogenous insulin levels enhancing glucose uptake into tissues from the bloodstream [8]. Regulation of muscle blood flow by insulin is an important physiological process as it controls the rate of glucose and insulin delivery to the myocyte [20,21]. In skeletal muscle of healthy people, physiological hyperinsulinaemia, either during a hyperinsulinaemiceuglycaemic clamp or elicited via mixed meal ingestion, stimulates both total-limb blood flow (macrovascular blood flow) and MBF [10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…Although intravenous glucose infusion leads to impaired limb arterial blood flow in healthy individuals (10), glucose levels were clamped to a much higher level (15 mmol/L sustained over 2 h) than that observed in the current study (~7.4 mmol/L peak). It is also possible that the intravenous nature of glucose and insulin infusion, bypassing the gut and subsequent release of many gut-derived hormones, is likely to elicit considerably different hemodynamic responses from that of oral macronutrient ingestion (38,42). For example, a 2-h intravenous hyperglycemic clamp (15 mmol/L) in healthy individuals leads to increased systolic and diastolic blood pressure and decreased leg arterial blood flow (10,27).…”
Section: Discussionmentioning
confidence: 99%
“…This is important, as the exogenous and endogenous glycaemic and hormonal responses elicited by orally ingested nutrients and intravenous insulin and glucose infusion are markedly different (Mingrone et al 2020). Therefore, the microvascular responses are likely to vary when comparing intravenous infusions and orally ingested nutrients (Roberts-Thomson et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the microvascular responses are likely to vary when comparing intravenous infusions and orally ingested nutrients (Roberts‐Thomson et al . 2020).…”
Section: Introductionmentioning
confidence: 99%